Exquisite specificity of Pks13 defines the essentiality of trehalose in mycobacteria - Yushu Chen; Justin Dao Tian Lim; Shu-Sin Chng (Proceedings of the National Academy of Sciences, 2026)
Mycolic acids (MAs) are the major component of the mycobacterial outer membrane, a key contributor to the intrinsic resistance of mycobacteria to external insults including multiple antibiotics. After being synthesized in the cytoplasm and before reaching the outer membrane, MAs are transported across the inner membrane in the form of an acylated sugar, generally believed to be trehalose monomycolates (TMMs). Whether trehalose is the only mycolate carrier during transport is under debate, and why this highly abundant disaccharide is essential for mycobacterial growth is unclear. To address these questions, we leveraged a trehalose auxotrophic Mycobacterium smegmatis strain to investigate the biosynthetic steps affording TMMs. We show that in addition to TMMs, mature MAs are also not produced in the absence of intracellular trehalose. This is likely due to a product inhibition mechanism where unreduced MA precursors accumulate on Pks13, the protein catalyzing the ligation of mycolic acids and the sugar head group. We establish that the unreduced mycolates could only be released by trehalose, revealing exquisite Pks13 specificity, and subsequently reduced by CmrA in vitro. Furthermore, only trehalose and its analogs can reactivate MA biosynthesis in cells. Finally, by replacing trehalose with a 6-deoxy analog in cells, we demonstrate that the cord factor trehalose dimycolate is dispensable for M. smegmatis growth in vitro. Our work gives a clear depiction of how TMMs are formed and provides a compelling reason for the essentiality of trehalose, shedding light on the development of future antimycobacterial strategies.